Analysis of Military and Political Security Issues in the Kurdistan Region _ Iraq Based on the Barry Buzan’s Theory After 2017 - Salih Omar Issa; Parwez Rahim Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In this study, we have tried to show the security threats to the political and military security of the Kurdistan Region by taking advantage of Bozan’s theory. Because by presenting five areas and the security sector (Political, Military, Societal, Economic and Environmental) besides presenting the framework of the "Regional Security complex theory", Bozan can present the threats and dangers of local and external political and military. Apart from the introduction, this research, explains Bozan’s view of military and political security and then talks about the political and military threats to the Kurdistan Region. Finally, we came to some conclusions, the most important of Political depth confrontation and military problems have a negative impact on the security of the Kurdistan Region. On the one hand, the threats and conflicts between Iran and the United States on the one the other hand, the military threats by Iran and Turkey to the Kurdistan Region, threaten the security of the Kurdistan Region.